The gut microbiota as a target to improve health conditions in a confined environment - Chen, Zheng; Wang, ZiYing; Li, Dan; Zhu, Beiwei; Xia, Yongjun; Wang, Guangqiang; Ai, Lianzhong; Zhang, Chunhong; Wang, Chuan (Frontiers in Microbiology, 2022)
Confined environments increase psychological stress and lead to health problems such as abnormal mood and rhythm disruption. However, the mechanism by which confined environments impact health has remained unclear. Significant correlations have been reported between psychological stress and changes in gut microbiota. Therefore, we investigated the effect of a confined environment on the composition of the gut microbiota, and analyzed the correlation between gut microbiota and health indicators such as uric acid (UA), sleep, and mood. We found that the gut microbiota of the subjects clustered into two enterotypes (Bi and Bla), and that the groups differed significantly. There were notable differences in the abundances of genera such as Bifidobacterium, Dorea, Ruminococcus_torques_group, Ruminococcus_gnavus_group, Klebsiella, and UCG-002 (P < 0.05). A confined environment significantly impacted the subjects’ health indicators. We also observed differences in how the subjects of the two enterotypes adapted to the confined environment. The Bi group showed no significant differences in health indicators before and after confinement; however, the Bla group experienced several health problems after confinement, such as increased UA, anxiety, and constipation, and lack of sleep. Redundancy analysis (RDA) showed that UA, RBC, mood, and other health problems were significantly correlated with the structure of the gut microbiota. We concluded that genera such as UCG-002, Ruminococcus, CAG352, and Ruminococcus_torques_group increased vulnerability to confined environments, resulting in abnormal health conditions. We found that the differences in the adaptability of individuals to confined environments were closely related to the composition of their gut microbiota.